Qualitative and quantitative characterization of the Surma cattle population in the Bench Maji Zone, Southwest Ethiopia - Fetene, Gedefaw; Alemayehu, Wondmagegn Kefyalew; Kebede, Damitie; Birara, Teshale Dereje (Frontiers in Animal Science, 2025)
The Surma cattle population is one of Ethiopia’s indigenous cattle populations with valuable qualitative and quantitative traits. This study aimed to identify the phenotypic characteristics of the Surma cattle population under farmers’ management conditions. A total of 384 Surma cattle were randomly sampled for the study of phenotypic traits. A purposive, multi-stage, stratified random sampling technique was used to determine the number of districts, kebeles, and households. Data were gathered through field observations and linear body measurements from the study population based on sex, district, and production system. The coat color of Surma cattle was spotted (82%), followed by patchy (12.2%) and plain (5.2%). The overall mean values for body weight (BW), chest girth (CG), body length (BL), height at the withers (HW), rump height (RH), rump length (RL), ear length (EL), and horn length (HL) were 223.54 ± 20 kg, 149.15 ± 7.16 cm, 108.60 ± 7.3 cm, 112.65 ± 7.5 cm, 111.34 ± 7.11 cm, 20.05 ± 1.6 cm, 18.48 ± 1.25 cm, and 25.00 ± 6.6 cm, respectively. The quantitative variables were significantly (p< 0.05) different between production systems, except for HL and EL, and all the measurements were significant (p< 0.05) between sexes. This study provides basic phenotypic information about Surma cattle for the first time, which is important for genetic study, conservation, and breed improvement. The Surma breed has a huge and well-framed body size in both male and female animals, which indicates that this breed may be used for beef breed improvement.